Longitudinal Alterations of Alpha-Synuclein, Amyloid Beta, Total, and Phosphorylated Tau in Cerebrospinal Fluid and Correlations Between Their Changes in Parkinson's Disease - Dolatshahi, Mahsa; Pourmirbabaei, Shayan; Kamalian, Aida; Ashraf-Ganjouei, Amir; Yaseri, Mehdi; Aarabi, Mohammad H. (Frontiers in Neurology, 2018)
Background: Parkinson's disease (PD) is characterized by proteinopathies and these proteinopathies seem to interact synergistically and lead to protein aggregations and changes in protein cerebrospinal fluid (CSF) levels. In this study, we aimed to explore the longitudinal changes of CSF alpha-synuclein (α-syn), total tau (t-tau), phosphorylated tau (p-tau), and beta-amyloid (Aβ 1-42) and their relationships with each other and with baseline clinical entities like REM sleep behavior disorder (RBD), cognitive impairment, motor symptoms, and olfaction dysfunction. Method: 112 non-demented PD patients and 110 controls were recruited from Parkinson's Progression Markers Initiative (PPMI). We used a linear mixed model within groups to assess longitudinal protein changes over six and twelve months and a random regression coefficient within the linear mixed model to investigate the correlation between proteins and their baseline clinical characteristics. Results: P-tau was lower in PDs only at baseline, but during a year, p-tau increased more rapidly in PDs than controls. Aβ 1-42 was not significantly different between groups at any separate timepoint; however, when assessed longitudinally, Aβ 1-42 showed significant changes in both groups. Conversely, t-tau and α-syn differed significantly between groups, but their longitudinal changes were not significant in either of the groups. Moreover, all proteins' baseline levels, except p-tau, could determine estimated longitudinal tau changes. Baseline RBDSQ scores but not UPDRS III, MoCA, or UPSIT scores were predictive of the longitudinal increase in α-syn levels. Conclusion: Longitudinal changes in levels of CSF proteins are related to each other and could help researchers further understand PD pathology. In addition, RBD seems to be a potential prognostic factor for PD progression. However, in order to reach a consensus, longer follow-up times are required.